TRANSPORTATION PLANNING AND THE USE OF TRANSCAD - van der Waerden, Peter; Timmermans, Harry (Transportes, 1996)
Transportation planning consists of a variety of activities that can be supported by Geographical Information Systems (GIS). This kind of system offers many functions that can be used for both spatial and transportation analyses. TransCAD is a GIS-package with specific transportation analysis tools. This package offers different functions for network analysis, transportation modeling, route analysis and traffic assignment. This paper describes the role of GIS for transportation planning which will be illustrated by several research projects. Special attention is given to the functions TransCAD offers for transportation analysis purposes. Three projects conducted by the Urban Planning Group of the Eindhoven University of Technology illustrate some of these functions in more detail. The projects concern the simulation of activity patterns, the evaluation of planning scenarios, and the simulation of parking behavior. Experiences from several research projects show that TransCAD is very useful for transportation planning activities. The open architecture that makes it possible to implement any self-made procedure in the TransCAD environment appears to be one of the most important characteristics of this software. Also the amount of network analyses such as shortest path finding and traffic assignment makes the package valuable. Still, improvements are desirable, for example a better structured users' manual, more advanced options for presentation and for modeling and statistical fitting of distribution. Some of these requests are implemented in the new Windows version of TransCAD 3.0.